NUMERICAL STUDIES OF MAGNETIC FIELD DYNAMICS IN HEMISPHERICAL ELECTRODES PLASMA FOCUS - Fairuz Diyana Ismail; Saktioto ' (Universitas Riau, 2014)
This study is aimed to numerically and experimentally investigate the magnetic field dynamics in hemisphericalelectrodes plasma focus. We have initiated the numerical magnetic field propagation by finite differenceapproach with Taylor expansion for the purpose of each distribution to plasma focus medium but not specifiedfor hemispherical electrodes design. Although the magnetic field profile is still in arbitrary numbers, this modelcan simply be used to compare with the experimental results. The absorption and attenuation of magnetic fieldare affected by the plasma medium mainly the production of electron and charged particle movement. However,the code generated for magnetic field attenuation is assumed for dimension and time dependant only.